TANGRAM como un Recurso Educativo - Lopez, Daniela; Álvarez, José (CIEX JOURNAL, 2017)
Pedagogy in Foreign Language Teaching is primarily aided in didactics, oriented to techniques and methodologies to achieve a successful transmission inside the role of teaching learning. When it comes to a different language, the degree of complexity is accentuated, so the teacher must make a big effort in transmitting knowledge. Tangram, for instance, is useful and has different application areas of application within teaching.